Climate Variations vs. Human Activities: Distinguishing the Relative Roles on Vegetation Dynamics in the Three Karst Provinces of Southwest China - Yang, Hao; Hu, Jing; Zhang, Shuo; Xiong, Ling; Xu, Yong (Frontiers in Earth Science, 2022)
Vegetation in karst areas is crucial for maintaining fragile local ecosystems, driven by climate change and human activities. Southwest China contains the largest continuous karst zone in the world and its vegetation dynamics are more sensitive to climate changes and human activities. However, previous studies rarely studied the driving roles of vegetation dynamics in karst areas during the last 20 years, and whether climate change or human disturbance factors have dominated the vegetation dynamics are still uncertain. The objective of this work is to study vegetation dynamics and its responses to climate change and human activities from 2001 to 2019 using the normalized difference vegetation index (NDVI). Taking the three karst provinces of southwest China as study area. Vegetation variation characteristics under the influence of climate variations and human activities were distinguished through a residual analysis. The results indicated general greening trends with about 90.31% of the study area experiencing an increase in NDVI and about 9.69% of the area showing a decrease. Within the combination of climate change and human activities, human activities became the dominant factor in the process of vegetation cover improvement and degradation in the study area during 2001–2019, with average relative roles of 62 and 59%, respectively. Temperature made the greatest positive contribution among the climatic factors, followed by precipitation and relative humidity. In contrast, sunshine duration had a negative effect on NDVI in the study area. Human activities have had different effects on the vegetation dynamics of the three karst provinces in southwest China, including destruction of vegetation around some cities.